Posterior Glenoid Wear in Total Shoulder Arthroplasty: Eccentric Anterior Reaming Is Superior to Posterior Augment. Issue 12 (December 2015) - Wang, Tim; Abrams, Geoffrey D.; Behn, Anthony W.; Lindsey, Derek; Giori, Nicholas; Cheung, Emilie V.
Abstract: Background: Uncorrected glenoid retroversion during total shoulder arthroplasty may lead to an increased likelihood of glenoid prosthetic loosening. Augmented glenoid components seek to correct retroversion to address posterior glenoid bone loss, but few biomechanical studies have evaluated their performance. Questions/purposes: We compared the use of augmented glenoid components with eccentric reaming with standard glenoid components in a posterior glenoid wear model. The primary outcome for biomechanical stability in this model was assessed by (1) implant edge displacement in superior and inferior edge loading at intervals up to 100, 000 cycles, with secondary outcomes including (2) implant edge load during superior and inferior translation at intervals up to 100, 000 cycles, and (3) incidence of glenoid fracture during implant preparation and after cyclic loading. Methods: A 12°‐posterior glenoid defect was created in 12 composite scapulae, and the specimens were divided in two equal groups. In the posterior augment group, glenoid version was corrected to 8° and an 8°‐augmented polyethylene glenoid component was placed. In the eccentric reaming group, anterior glenoid reaming was performed to neutral version and a standard polyethylene glenoid component was placed. Specimens were cyclically loaded in the superoinferior direction to 100, 000 cycles. Superior and inferior glenoid edge displacements were recorded. Results: Surviving specimens in the posterior augment group showed greater displacement than the eccentric reaming group of superior (1.01 ± 0.02 [95% CI, 0.89‐1.13] versus 0.83 ± 0.10 [95% CI, 0.72‐0.94 mm]; mean difference, 0.18 mm; p = 0.025) and inferior markers (1.36 ± 0.05 [95% CI, 1.24‐1.48] versus 1.20 ± 0.09 [95% CI, 1.09‐1.32 mm]; mean difference, 0.16 mm; p = 0.038) during superior edge loading and greater displacement of the superior marker during inferior edge loading (1.44 ± 0.06 [95% CI, 1.28‐1.59] versus 1.16 ± 0.11 [95% CI, 1.02‐1.30 mm]; mean difference, 0.28 mm; p = 0.009) at 100, 000 cycles. No difference was seen with the inferior marker during inferior edge loading (0.93 ± 0.15 [95% CI, 0.56‐1.29] versus 0.78 ± 0.06 [95% CI, 0.70‐0.85 mm]; mean difference, 0.15 mm; p = 0.079). No differences in implant edge load were seen during superior and inferior loading. There were no instances of glenoid vault fracture in either group during implant preparation; however, a greater number of specimens in the eccentric reaming group were able to achieve the final 100, 000 time without catastrophic fracture than those in the posterior augment group. Conclusions: When addressing posterior glenoid wear in surrogate scapula models, use of angle‐backed augmented glenoid components results in accelerated implant loosening compared with neutral‐version glenoid after eccentric reaming, as shown by increased implant edge displacement at analogous times. Clinical Relevance: Angle‐backed components may introduce shear stress and potentially compromise stability. Additional in vitro and comparative long‐term clinical followup studies are needed to further evaluate this component design.